2000
DOI: 10.1021/cm0002416
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Highly Ordered CF2-Rich Films Using Continuous Wave and Pulsed Hexafluoropropylene Oxide Plasmas

Abstract: The structure and composition of fluorocarbon materials deposited in pulsed and continuous wave (CW) hexafluoropropylene oxide (HFPO) plasmas were investigated. Results indicate substantial dependence on substrate position relative to the rf coil. When the substrate was placed 8 cm downstream from the rf coil (25 W CW), highly amorphous, cross-linked films were obtained. In contrast, materials deposited 28 cm downstream from the rf coil contained less cross-linked moieties and a higher degree of order. Angle-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 25 publications
4
72
1
Order By: Relevance
“…Over the past 5 years, we have studied a variety of fluorocarbon systems, including C 2 F 6 , C 2 F 6 /H 2 , CHF 3 [45], hexafluoropropylene oxide (HFPO) [46], C 6 F 6 , and 1,2,4-C 6 H 3 F 3 plasmas [47]. Most recently, we have focused on C 3 F 8 and C 4 F 8 plasmas as these systems are finding increased use in the microelectronics industry because of their lower global warming potentials [48].…”
Section: Fluorocarbon Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 5 years, we have studied a variety of fluorocarbon systems, including C 2 F 6 , C 2 F 6 /H 2 , CHF 3 [45], hexafluoropropylene oxide (HFPO) [46], C 6 F 6 , and 1,2,4-C 6 H 3 F 3 plasmas [47]. Most recently, we have focused on C 3 F 8 and C 4 F 8 plasmas as these systems are finding increased use in the microelectronics industry because of their lower global warming potentials [48].…”
Section: Fluorocarbon Plasmasmentioning
confidence: 99%
“…Under the same deposition conditions, films formed in C 3 F 8 plasmas are less cross-linked (defined as %CF ϩ %C-CF x ϩ %C-H), with higher CF 2 content and F/C ratios than those deposited in C 4 F 8 plasmas. We have also found that films deposited even further downstream (i.e., 28 cm from the glow) have significantly lower cross-linking as do films deposited at lower applied rf powers [22,46].…”
Section: Fluorocarbon Plasmasmentioning
confidence: 99%
“…These results demonstrated that the increase in the distance between substrate and inlet gas leads to an increase in the hydrophobicity of a surface. Butoi et al [91] studied the effect of distance from a RF coil on the structure of a plasma polymerized Hexafluoropropylene oxide film. Their results showed that at a short distance, a cross-linked and amorphous film was obtained, while at a greater distance a linear and higher degree of order film was obtained.…”
Section: Ii-4-5-influence Of Distance From Monomer Inlet On Wettabilitymentioning
confidence: 99%
“…Therefore, the absence of charged particles leads to orientation of the chains and networks of a coating characterized by a low surface energy [73]. Butoi et al [91] have also found that depositions performed at the farthest distance from the plasma glow discharge of Hexafluoropropylene oxide (HFPO) displayed a high degree of orientation. They showed that the free movement of undesired energetic species bombardment occurs simply at high distance because these species are lost through plasma recombination processes prior to reaching a substrate.…”
Section: ïV-3-optimization Of Plasma Process Parametersmentioning
confidence: 99%
“…Recently, several groups have demonstrated that increased chemical character of the desired polymer functional group is retained if the if plasma source is pulsed at frequencies in the hertz to kilohertz range. [7,8,9] Models have predicted that pulsing the discharge may be a unique means to controlling the kinetic processes in the plasma. [ 10] However, the mechanisms that lead to the plasma deposition of high quality functional polymers are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%